NATURAL RADIONUCLIDES IN RESIDUES FROM NON-NUCLEAR INDUSTRIES - E. P. Lisachenko; I. P. Stamat (Радиационная гигиена)
In the present overview we analyze the available data concerning residues from non-nuclear industries which contain naturally occurring radioactive material (NORM). We consider their quantity, radiation properties, placement, utilization, regulatory and management.